Rapid Prototyping applied to surgical planning for correcting craniofacial malformations in wild animals. A case study of a brazilian fox - Freitas, E. P. [UNESP]; Teixeira, Carlos Roberto [UNESP]; Rahal, Sheila Canevese [UNESP]; Villela, C. H. S.; Silva, J. V. L.; Noritomi, P. Y.; Yamashita, S. (Taylor & Francis Ltd, 2008)
Veterinary surgery for treatment of wild animals is becoming an increasingly demanding task because it involves animals of different anatomy, many of them are already stressed and treatment must be performed to the highest standard in the minimum period of time. Craniofacial alterations may occur for three main reasons: genetic, functional or a combination of both. It is possible to modify the functional cause using intraoral devices like inclined plane. The treatment planning can be made based on virtual 3D models and rapid prototyping. An approximately 9 months old, 3.7 kg male Brazilian fox (Lycalopex vetulus) was referred to the Veterinary Hospital. Physical examination showed malocclusion with a deviation of the mandible to the right side. The virtual 3D model of the head was generated based on CT image data. The 3D models and rapid prototyping opened up new possibilities for the surgical planning and treatment of wild animals.